Intergenic transcription in the human beta-globin gene cluster. - Plant, K; Routledge, S; Proudfoot, N (2001)
Our previous studies on nascent transcription across the human beta-globin gene cluster revealed the presence of intergenic transcripts in addition to the expected genic transcripts. We now show that transcription into the beta-globin locus control region (LCR) begins within an ERV9 endogenous retroviral long terminal repeat upstream of DNase I hypersensitive site 5. However, in a transgenic mouse, which has the human beta-globin LCR but lacks the ERV9 LTR, transcription begins upstream of the transgenic locus. We postulate that in this transgenic mouse nearby endogenous mouse promoters are activated by the LCR. Intergenic transcription is also detected across the whole transgenic globin gene locus independently of the stage of erythroid development. Intergenic transcription in the beta-globin cluster is erythroid specific; however, it can be induced in nonerythroid cells by several means: by transinduction with a plasmid transcribing part of the cluster, by exogenous addition of transcription factors, and by treatment with the histone deacetylase inhibitor trichostatin A.